8 - An Assessment of Labour Market Information Systems in Southern Africa: 10.4314/ad.v26i2.22147 - Sparreboom, Théo (Africa Development, 2001)
This paper examines the role of information systems in relation to employment and labour policies in southern Africa. Three functions of information systems are distinguished: the description function, the monitoring function and the evaluation function. It will be shown that the role of information systems has often been limited to the description function, which signifies an important mismatch between information and policies. Reducing this mismatch not only requires additional resources for data collection, but also more attention for appropriate institutional arrangements for information systems and the structure of labour markets in southern Africa. This is illustrated with a case study of the development of information systems for skills policies in South Africa.